PENDEKATAN PSIKOLOGIS DALAM UPAYA MENGATASI KECANDUAN PENYALAHGUNAAN NARKOTIKA - Rois Nafi'ul Umam; Sutya Dewi; Intan Belinda Cahyana; Miftahul Jannah (Sekolah Tinggi Agama Islam Taruna Surabaya, 2021)
Happiness and serenity in living life is the hope of every individual, to achieve this there are many things that can be done, one of which is like increasing worship to Allah, but not all individuals have the same thoughts, there are individuals who choose to achieve happiness and tranquility by abusing it. illegal drugs such as narcotics. The purpose of this study was to describe the role of a psychological approach as an effort to overcome addiction for narcotics abusers. The method used in this research is a qualitative method with a literature study approach by tracing and reviewing several documents in the form of journals and books. From the analysis carried out, the psychological approach plays a role in rehabilitating narcotics abusers through the activity of reading the Koran, prayer therapy and giving tausiah.